Design guideline for thermal comfort in terrace houses in Malaysia [microfilm] m - Ang, Huey Ying (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Senibina)) - Universiti Teknologi Malaysia, 2007